USING EXPERIENCE AND MODERN APPROACHES TO SELECTION OF ADAPTED FORMULA MILK FOR CHILDREN ON ARTIFICIAL FEEDING - N. E. Sannikova; T. V. Borodulina; L. Н. Malyamova; O. S. Shelestovskaya; N. A. Belokonova; T. A. Martynova; N. S. Sokolova (Вопросы современной педиатрии, 2014)
Background: Modern approaches to feeding the children in the first year of life, especially when the artificial formula milk is indicated, necessitate the individual approach to the selection of formula in order to adequately provide the organism with micro- and macronutrients. Aim: The purpose of the study was to evaluate the effect of examined formula milk enriched in pro- and prebiotics on growth and development of the children in the first year of life. Patients and methods: The participants of the study were 75 children in the age between 1 and 5 months at the different feeding types. Group I (n = 25) was given a standard adapted formula milk, Group II (n = 24) — standard formula milk of the same brand, Group III (n = 26) — breast milk. Results: The study showed that when feeding with the breast milk body weight deficiency was observed in 19.4% of children, while body weight excess — in 15.4% of children. When feeding with the artificial milk, the excessive body weight was observed in 18.4%, while the body weight deficiency was recorded only in 12.2% of children. The analysis of examination results of children in the first year of life on the different feeding types showed the positive effect of the adapted formula milk on the health and development indices: the number of children with optimal physical and neuropsychic development has grown (from 72 to 88%), the functional condition of the gastrointestinal tract has recovered (posseting has reduced from 88 to 16% cases, flatulence — from 36 to 4%, intestinal constipation — from 60 to 4%, stool disorders — from 36 to 4%). Conclusion: The examined adapted formula milk can be successfully used in children in the first year of life when breast feeding is impossible.